Antimicrobial Resistance Patterns and Plasmid Profiles of Staphylococcus Aureus Isolated from Different Clinical Specimens in Saudi Arabia - Adnan S. Jaran (European Scientific Journal, ESJ, 2017)
The aims of this study were to investigate antibiotic resistance patterns and plasmid profile of antibiotic resistant Staphylococcus strains isolated from clinical specimens, and to find out a possible relationship between plasmids profile and antibiotic sensitivity patterns. Staphylococcus strains were isolated from different clinical specimens from different hospitals and primary health care centers. Antimicrobial susceptibility of Staphylococcus isolates was determined using disc diffusion method against 10 commonly used antimicrobial drugs. Plasmid DNA was extracted from lysed Staphylococcus cells using Plasmid Miniprep kit, and visualized using Agarose gel electrophoresis. The results showed that isolated strains of Staphylococcus were resistant to Penicillin (61%), Erythromycin (45%), Chloramphenicol (21%) and Co-trimoxazole (15%). Plasmid analysis of clinical isolates showed the presence of 0 to 3 plasmids with size range of 2 to 31 Kb, as compared to control Staphylococcus aureus ATCC 25923 which showed 4 plasmids (size range of 2 to 21 Kb). The results obtained in this study showed no direct correlation between the patterns of antibiotic resistance and plasmid profiles.